Eruptive activity at Turrialba volcano (Costa Rica): Inferences from 3He/4He in fumarole gases and chemistry of the products ejected during 2014 and 2015 - Di Piazza, Andrea (2016)
A new period of eruptive activity started at Turrialba volcano, Costa Rica, in 2010 after almost 150 years of quiescence. This activity has been characterized by sporadic explosions whose frequency clearly increased since October 2014. This study aimed to identify the mechanisms that triggered the resumption of this eruptive activity and characterize the evolution of the phenomena over the past 2 years. We integrate 3He/4He data available on fumarole gases collected in the summit area of Turrialba between 1999 and 2011 with new measurements made on samples collected between September 2014 and February 2016. The results of a petrological investigation of the products that erupted between October 2014 and May 2015 are also presented. We infer that the resumption of eruptive activity in 2010 was triggered by a replenishment of the plumbing system of Turrialba by a new batch of magma. This is supported by the increase in 3He/4He values observed since 2005 at the crater fumaroles and by comparable high values in September 2014, just before the onset of the new eruptive phase. The presence of a number of fresh and juvenile glassy shards in the erupted products increased between October 2014 and May 2015, suggesting the involvement of new magma with a composition similar to that erupted in 1864–1866. We conclude that the increase in 3He/4He at the summit fumaroles since October 2015 represents strong evidence of a new phase of magma replenishment, which implies that the level of activity remains high at the volcano.